Implementation of Multicultural Education at the Asy-Syifa Tsanawiyah Madrasah Balikpapan - Dimas Ramadhan; Iskandar Yusuf (al-Afkar, Journal For Islamic Studies, 2024)
Multicultural education refers to a term that can be used to describe the challenges and issues related to education in a multicultural society, both in descriptive and normative aspects. Additionally, this concept encompasses an understanding of policy considerations and strategies for multicultural education. The current focus of multicultural education is not only limited to racial, religious, and mainstream cultural groups. Instead, greater attention is given to intercultural education aimed at enhancing understanding and tolerance among individuals from minority groups that have integrated into the mainstream society. MTS Asy-Syifa Balikpapan distinguishes itself in the implementation of multicultural education compared to other schools. The fundamental concept of MTS Asy-Syifa is a boarding school, so it not only imparts instruction and implements multicultural education for all its students but also applies it in daily life within the school environment and beyond. The implementation of multicultural education at MTS Asy-Syifa is not only focused on the learning process but also includes aspects of daily life, creating an environment that supports diversity and tolerance among students.